Application Of Hyperoxygenation Before And After Suctioning To Prevent Hypoxemia In Mechanically Ventilated Patients At X Hospital, Jakarta - Annisa Suciyati (International Journal of Health Engineering and Technology, 2026)
Respiratory failure with sepsis is a critical condition that requires mechanical respiratory support (ventilator). Endotracheal Tube (ETT) placement and decreased consciousness trigger sputum hypersecretion and suppress the cough reflex, thus causing the problem of Ineffective Airway Clearance. Suctioning procedure is mandatory, but the negative pressure is at risk of causing transient hypoxemia. Evidence-based intervention through 100% hyperoxygenation before (pre) and after (post) suctioning is needed to maintain the stability of tissue oxygenation. To analyze the implementation of 100% hyperoxygenation interventions before and after suctioning in addressing the problem of Ineffective Airway Clearance in patients with respiratory failure with sepsis in the intensive care unit. The study design used a comparative case study on two critically ill patients who were ventilated in Synchronized Intermittent Mandatory Ventilation (SIMV) mode. Patient I (Mrs. F, 56 years old) experienced respiratory failure ec Pneumonia (Klebsiella pneumoniae) with a history of Pulmonary TB, and Patient II (Mr. H, 63 years old) experienced respiratory failure ec Aspiration Pneumonia post-stroke. The intervention given was the administration of 100% FiO_2 via a ventilator for 1–2 minutes before and after suctioning. The results of implementation in both patients showed that the hyperoxygenation protocol was able to protect patients from the risk of severe hypoxia. In Patient I, there was a temporary decrease in oxygen saturation (SpO_2) to 93% when the catheter was inserted, but it recovered to 99% in less than 1 minute after hyperoxygenation. In Patient II, the perfusion status was stable with a consistent SpO_2 of 98%–100% without transient tachycardia or cyanosis. Administering 100% hyperoxygenation before and after suctioning is effective in maintaining oxygen saturation stability, accelerating re-expansion of collapsed alveoli, and preventing hypoxemic complications in respiratory failure patients using mechanical ventilation.